Temporal small RNA transcriptome profiling unraveled partitioned miRNA expression in developing maize endosperms between reciprocal crosses - Xin, Mingming; Yang, Guanghui; Yao, Yingyin; Peng, Huiru; Hu, Zhaorong; Sun, Qixin; Wang, Xiangfeng; Ni, Zhongfu (Frontiers in Plant Science, 2015)
In angiosperms, the endosperm nurtures embryo and provides nutrients for seed germination. We have performed high-throughput small RNA transcriptome sequencing of kernels at 0, 3, and 5 days after pollination (DAP) and endosperms at 7, 10, and 15 DAP by using B73 and Mo17 reciprocal crosses in previous study. Here, we further explored these small RNA-seq data to investigate the potential roles of miRNAs in regulating gene expression process. In total, 57 conserved miRNAs and 18 novel miRNAs were observed highly expressed in maize endosperm. Temporal expression profiling indicates these miRNAs exhibited dynamic and partitioned expression patterns at different developmental stages between maize reciprocal crosses, and qRT-PCR results further confirmed our observation. In addition, we found a subset of distinct tandem miRNAs are generated from a single stem-loop structure in maize which might be conserved in monocots. Furthermore, a SNP variation of Zma-miR408-5p at 11th base position was characterized between B73 and Mo17 which leads to completely different functions in repressing targets. More interestingly, Zma-miR408-5p exhibited B73-biased expression pattern in the B73 and Mo17 reciprocal hybrid endosperms at 7, 10 and 15 DAP according to the reads abundance with SNPs and CAPS experiment.